Metal-Organic Frameworks as Versatile Heterogeneous Solid Catalysts for Henry Reactions - Cirujano, Francisco G.; Luque, Rafael; Dhakshinamoorthy, Amarajothi (Molecules (Basel, Switzerland), 2021)
Metal–organic frameworks (MOFs) have become one of the versatile solid materials used for a wide range of applications, such as gas storage, gas separation, proton conductivity, sensors and catalysis. Among these fields, one of the more well-studied areas is the use of MOFs as heterogeneous catalysts for a broad range of organic reactions. In the present review, the employment of MOFs as solid catalysts for the Henry reaction is discussed, and the available literature data from the last decade are grouped. The review is organized with a brief introduction of the importance of Henry reactions and structural properties of MOFs that are suitable for catalysis. The second part of the review discusses the use of MOFs as solid catalysts for the Henry reaction involving metal nodes as active sites, while the third section provides data utilizing basic sites (primary amine, secondary amine, amides and urea-donating sites). While commenting on the catalytic results in these two sections, the advantage of MOFs over other solid catalysts is compared in terms of activity by providing turnover number (TON) values and the structural stability of MOFs during the course of the reaction. The final section provides our views on further directions in this field.